A Sensitive Broadband (UV–vis–NIR) Perovskite Photodetector Using Topological Insulator as Electrodes. Issue 4 (12th December 2018) - Liang, Feng‐Xia; Liang, Lin; Zhao, Xing‐Yuan; Luo, Lin‐Bao; Liu, Yu‐Hung; Tong, Xiao‐Wei; Zhang, Zhi‐Xiang; Huang, J. C. Andrew
Abstract: Here, a sensitive and broadband perovskite photodetector is developed by using crystalline topological insulator (TI) Bi2 Se3 film as the electrode, which is synthesized by molecular beam epitaxy (MBE). The as‐fabricated Bi2 Se3 ‐FA0.85 Cs0.15 PbI3 ‐Bi2 Se3 photodetector exhibits apparent sensitivity to 650 nm illumination with an on/off ratio of 0.8 × 10 5 and good reproducibility. The responsivity, external quantum efficiency, and specific detectivity are estimated to be 8.4 A W −1, 1604%, and 1.7 × 10 13 Jones, respectively, which are better not only than the perovskite device using Au as electrode, but also than the majority of other perovskite materials based devices. It is also interesting to find that the TI based perovskite photodetector displays obvious photoresponse to near infrared light (NIR) with 980 nm due to contribution of TI Bi2 Se3 layer. It is believed that the present TI based perovskite photodetector holds promise for broadband and high‐performance optoelectronic applications in the future. Abstract : A broadband photodetector assembled from FA0.85 Cs0.15 PbI3 perovskite and topological insulator (Bi2 Se3 film) is demonstrated. The as‐assembled device exhibits very obvious photoresponse with peak sensitivity at 650 nm with a responsivity of 8.4 A W −1 . The corresponding eternal quantum efficiency, detectivity, and on/off ratio are estimated to be 1604%, 1.7 × 10 13 Jones, and 0.8 × 105, respectively.